Near-IR organic sensitizers containing squaraine and phenothiazine units for dye-sensitized solar cells. (February 2015) - Bae, Seong Hee; Seo, Kang Deuk; Choi, Won Seok; Hong, Ji Yeoun; Kim, Hwan Kyu
Abstract: Unsymmetrical squaraine near-infrared (NIR) sensitizers with variable π-bridge units, based on the donor-π-squaraine core-acceptor structural motif, were synthesized and used as sensitizers for dye-sensitized solar cells. The phenothiazine as a donor group was linked to a squaraine core unit using various thiophene derivatives. Among them, three squaraine-based sensitizers have a carboxylic acid group as an electron-accepting group directly attached to the squaraine component, while one of four squaraine-based sensitizers has a cyanoacrylic acid as a more strongly electron-accepting group directly attached to the squaraine component. The sensitizers exhibited intense absorption in the NIR region and strong luminescence. The LUMO levels of the present squaraine-based sensitizers were slightly more negative than the conduction band edge of TiO2 photoanode. As a result, a solar cell based on the squaraine-based sensitizer containing a thiophene unit as a π-bridge unit and a carboxylic acid group as an electron-accepting group exhibited better photovoltaic performance with a J SC of 6.0 mA cm −2, a V OC of 448 mV, and an FF of 0.73, corresponding to an overall conversion efficiency η of 2.0%. Graphical abstract: Highlights: The squaraine-based dyes were synthesized and used as sensitizer for DSSCs. The phenothaizine donor was linked to a squaraine core unit using thiophene units. The sensitizers exhibited intense absorption in the NIR region. The LUMO levels of sensitizers were more negative than the conduction band of TiO2 .